2005
DOI: 10.1111/j.1365-313x.2005.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously occurring mutations in the cyclobutane pyrimidine dimer photolyase gene cause different sensitivities to ultraviolet‐B in rice

Abstract: SummarySensitivity to ultraviolet-B (UVB) radiation (280-320 nm) varies widely among rice cultivars. We previously indicated that UV-resistant rice cultivars are better able to repair cyclobutane pyrimidine dimers (CPDs) through photorepair than are UV-sensitive cultivars. In this paper, we report that UVB sensitivity in rice, in part, is the result of defective CPD photolyase alleles. Surjamkhi (indica) exhibited greater sensitivity to UVB radiation and was more deficient in CPD photorepair ability compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…We further found that the UV-sensitive Norin 1 is defective in CPD photoreactivation in vivo and in vitro (Hidema et al, 2000;Teranishi et al, 2004). A similar correlation between sensitivity to UV and a defective CPD photoreactivation was also observed in an UV-sensitive cultivar of Surjamkhi, the indica rice cultivar (Hidema et al 2001;Hidema et al, 2005). Clarifying the molecular nature of the deficiency of CPD photolyase in Norin 1, Surjamkhi, and other UV-sensitive rice cultivars, may help us to understand the structure and function of class II CPD photolyases.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…We further found that the UV-sensitive Norin 1 is defective in CPD photoreactivation in vivo and in vitro (Hidema et al, 2000;Teranishi et al, 2004). A similar correlation between sensitivity to UV and a defective CPD photoreactivation was also observed in an UV-sensitive cultivar of Surjamkhi, the indica rice cultivar (Hidema et al 2001;Hidema et al, 2005). Clarifying the molecular nature of the deficiency of CPD photolyase in Norin 1, Surjamkhi, and other UV-sensitive rice cultivars, may help us to understand the structure and function of class II CPD photolyases.…”
Section: Introductionsupporting
confidence: 54%
“…Sasanishiki is the most resistant to UV radiation followed by Norin 1, Surjamkhi and Gulfmont in this order. To understand the molecular nature of the difference in UV sensitivity, we cloned the CPD photolyase genes from Sasanishiki (Hirouchi et al, 2003), Norin 1 (Teranishi et al, 2004), Surjamkhi (Hidema et al, 2005), and Gulfmont (this study) as described in Materials and Methods. Figure 2 shows the alignments of amino acids derived from 4 rice caltivars, in which the Sasanishiki, Norin 1, and Surjamkhi CPD photolyase genes encode a 1521-bp ORF coding for 506 amino acid residues, and the Gulfmont CPD photolyase gene encodes a 1446-bp ORF coding for 481 amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among isolated Arabidopsis mutants exhibiting decreased UV resistance (UVR), UVR2 and UVR3 genes were, respectively, identified as CPD and (6-4) PHR (18,21,22). Studies in rice confirmed these fundamental assignments and identified polymorphisms among rice strains selected for UV tolerance (20,23,24), supporting the value of an improved knowledge of CPD2PHRs for understanding plant cell biology.…”
Section: Ozone Depletion Increases Terrestrial Solar Ultraviolet B (Umentioning
confidence: 56%
“…The sensitivity of rice (Oryza sativa) to UVB radiation varies among cultivars (Dai et al, 1992;Kumagai and Sato, 1992). We previously found that the CPD photorepair ability in UV-resistant rice is significantly higher than that in UV-sensitive rice and that this is due to an alteration of CPD photolyase activity resulting from spontaneously occurring mutations in the CPD photolyase gene (Teranishi et al, 2004;Hidema et al, 2005;Yamamoto et al, 2007). Furthermore, we recently generated transgenic rice plants bearing the CPD photolyase gene of the UVresistant rice cultivar 'Sasanishiki' in the sense orientation or the antisense orientation .…”
mentioning
confidence: 99%